Local perspectives on marine ecotourism development in a water-insecure island region: the case of Bocas del Toro, Panama - Kim, Abigael; Scott, Cinda P.; Swartz, Wilf (Frontiers in Marine Science, 2024)
As a dimension of a blue economy, marine ecotourism should, in theory, not only increase economic viability and environmental sustainability but, most importantly, pursue socially equitable outcomes. In tropical and sub-tropical island regions, where substantial tourism development is often coupled with widespread strains on public infrastructure and services, including water access, there exists a need to better understand the expansion of this industry is felt at the community level; more importantly by individuals who are reliant on these infrastructures and services. Through a case study of the Bocas del Toro Archipelago, where water insecurity is becoming acute, we draw on and mobilize stories from local community members, alongside non-participant observations and document collection, to 1) document the experience of some community members with water insecurity and shortages, including how they perceive the roles played by the central government and marine ecotourism sector, and 2) examine how community members feel about how communities feel about policies and investment priorities of the central government regarding water insecurity, including the extent to which they view marine ecotourism development as undermining or promoting local needs. Our results underline the complex nature of marine ecotourism governance and infrastructure development outcomes in a resource-insecure island region, demonstrating that current issues are greatly impacted by historical and social underpinnings of neo-colonialism and systemic racism, misalignments of community vs. government development priorities, and eroded political trust, that shape local experiences with sustainable development and local residents’ perceptions of the ability of marine ecotourism to address issues of water insecurity. Moreover, while our focus is on the marine ecotourism industry, the significance of these findings contributes to a growing body of literature that places local experiences at the forefront of research into the implications of sustainable development in island regions.